Flexible, Transparent, Conducting Films of Randomly Stacked Graphene from Surfactant-Stabilized, Oxide-Free Graphene Dispersions - DUESBERG, GEORG; COLEMAN, JONATHAN (My University, 2010)
We have exfoliated graphite in water to give dispersions of mono and few-layer graphene stabilised by surfactant. These dispersions can be used to form thin, disordered films of randomly stacked, oxide-free, few-layer graphenes. These films are transparent with a DC conductivity of up to 1.5'104 S/m. The conductivity is stable under flexing for at least 2000 cycles. The electrical properties are limited by disorder and aggregation suggesting future routes for improvement.
PUBLISHED
Keywords: Graphene; Transparent conducting film; Electron microscopy; Conductivity; Graphene, Transparent conducting film, Electron microscopy, Conductivity